Transient Inactivation of the Medial Prefrontal Cortex Affects Both Anxiety and Decision-Making in Male Wistar Rats - de Visser, Leonie; Baars, Annemarie; van 't Klooster, Jose; van den Bos, Ruud (Frontiers in Neuroscience, 2011)
In both humans and rats high levels of anxiety impair decision-making in the Iowa Gambling Task (IGT) in male subjects. Expression of the immediate early gene c-fos as marker of neural activity in rat studies indicated a role of the medial prefrontal cortex (prelimbic and infralimbic region; mPFC) in mediating the relationship between anxiety and decision-making. To delineate this relationship further and assess the underlying neurobiology in more detail, we inactivated in the present study the mPFC in male rats using a mixture of the GABA-receptor agonists muscimol and baclofen. Rats were exposed to the elevated plus maze (EPM) to measure effects on anxiety and to the rodent version of the IGT (r-IGT). Inactivation led to increased levels of anxiety on the EPM, while not affecting general activity. The effect in the r-IGT (trials 61-120) was dependent on levels of performance prior to inactivation (trial 41-60): inactivation of the mPFC hampered task-performance in rats, which already showed a preference for the advantageous option, but not in rats which were still choosing in a random manner. These data suggest that the mPFC becomes more strongly involved as rats have learned task-contingencies, i.e. choose for the best long-term option. Furthermore they suggest, along with the data of our earlier study, that both anxiety and decision-making in rats are mediated through a neural circuitry including at least the mPFC. The data are discussed in relation to recent data of rodent studies on the neural circuitry underlying decision-making.